PENGARUH PENERAPAN MODEL JUCAMA TERHADAP PRESTASI DAN EFIKASI DIRI PADA MATERI PECAHAN - kuncahyono Kuncahyono; Erna yayuk (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2019)
This study aims to examine the effect of the JUCAMA model on the learning outcomes of fifth grade elementary school students in fractional material and self-efficacy in fractions. The sample selection was chosen randomly as the experimental group and the control group. Data collection techniques for each group were given Reflection Symmetry Achievement Test (RSAT), and Fraction Self-Efficacy Scale (FSES) as pre-test and post-test. Covariance analysis was carried out to answer the research findings. In addition, five participants were interviewed to examine the source of self-efficacy which was a determinant of changes in the level of self-efficacy. The findings revealed that the JUCAMA model had a significant positive effect on student achievement in reflection and self-efficacy on fractional material.